Sustaining Integrity: The Role of Education and Macroeconomic Variables for Corruption Eradication - Indah Susilowati; Andi Kurniawan Karta Negara; Muhammad Syariful Anam; Hizbul Khootimah Az Zaakiyyah; Ramadhanti Dara Sakinah; Aini Nur Furoida (Universitas Negeri Malang, 2024)
This study aims to analyze the effect of education level and several macroeconomic variables on the corruption index in Asia-Pacific Economic Cooperation (APEC) member countries. This study uses the two-stage least square (2SLS) estimation method. This study found that the lifelong learning index, higher education participation, and foreign direct investment have a negative and significant effect on corruption in all APEC member countries and developing country members. Secondary education and government efficiency index have a negative and significant effect on corruption in all countries (all member states, developed and developing countries). GDP per capita and economic openness have a positive and significant effect on corruption levels in APEC member states and developing countries. The fight against corruption must be immediately implemented as a political influence. Delaying this will reduce the effectiveness of future policies. Institutional reforms bring more positive benefits in countries that are really fighting corruption.